The Influence of Tourism Experience and Online Reviews on Revisit Intention (A Study on the Tourism Business of Green Canyon Pangandaran) - Octavia, Fitriani; Sukoco, Iwan; Kurniawati, Linda (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Tourism destination marketing strategies not only focus on creating experiences for tourists, but also need to pay attention to public perception on digital platforms through online reviews. This study aims to determine the effect of tourism experience and online reviews on revisit intention at the Green Canyon tourism business in Pangandaran Regency, West Java. This study uses quantitative methodology and uses a questionnaire as a tool to collect data from 150 respondents. The target population of this study consists of tourists who have visited Green Canyon Pangandaran at least once in the last three years (2023-2025) and have seen or given online reviews related to Green Canyon Pangandaran tourism on Google Maps, Social Media, and other platforms. Data were analyzed using multiple linear regression. The results showed that tourism experience and online reviews simultaneously have a positive and significant influence on the intention to revisit the Green Canyon Pangandaran tourism business. This research enriches the tourism behavior literature and provides insights for tourism managers to develop marketing strategies that focus on improving the quality of tourism experiences and managing online reviews to strengthen tourists' revisit intentions.